Catalysts incorporating minute transition metals for gasoline engine exhaust gas treatment

By mixed with compositions that mixed with platinum and transition metal in the three -effect catalyst, the performance of existing catalysts in cold launch, combustion and air -fuel ratio windows in cold, and achieve the effect of improving performance and resource saving.

CN119365259APending Publication Date: 2025-01-24JOHNSON MATTHEY PLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380047613.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing three-effect catalysts are inadequate in the cold start stage, have poor ignition performance, and have poor air-fuel ratio window performance in the thermal transient stage. They rely on precious platinum group metal (PGM) resources, and there are resource waste and price fluctuations. risk.

Method used

The catalyst composition containing the platinum metal (PGM) components and the transition metal component, wherein the Moore of Platinum (PT) and the transition metal (FE or CU) is 0.2 to 10.0. performance.

Benefits of technology

The performance of the three-way catalyst in light-off and air-fuel ratio window performance tests has been improved, achieving higher economic benefits and environmental sustainability, and reducing reliance on precious PGM resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365259A_ABST
    Figure CN119365259A_ABST
Patent Text Reader

Abstract

A three-way catalyst article and its use in an exhaust system for an internal combustion engine are disclosed. A catalyst article for treating an exhaust gas, the catalyst article comprising: a substrate comprising an inlet end and an outlet end, having an axial length L; the present invention relates to a catalyst comprising a first catalytic region comprising a first platinum group metal (PGM) component and a first transition metal component wherein the first PGM component comprises platinum (Pt) and the first transition metal component is Fe or Cu, and wherein the molar ratio of Pt to the first transition metal is 0.2 to 10.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to catalytic articles useful for treating exhaust emissions from gasoline engines. Background Art

[0002] Internal combustion engines produce exhaust gases that contain a variety of pollutants, including hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (“NO x ”). Emission control systems that include exhaust gas catalytic conversion catalysts are widely used to reduce the amount of these pollutants emitted into the atmosphere. A common catalyst used for gasoline engine emission treatment is the TWC (three-way catalyst). The TWC performs three main functions: (1) oxidation of CO; (2) oxidation of unburned HC; and (3) oxidation of NO x restoration.

[0003] Despite advances in TWC technology, certain engine platforms still require improved catalytic converters to simultaneously improve cold start performance, provide higher light-off performance, and provide better window performance in terms of air-fuel ratio (A / F) during hot transients. It is necessary to flexibly use Pd and / or Pt in TWCs to mitigate the potential risk of PGM price fluctuations and to conserve and effectively use natural resources of PGMs. Specifically, Pt has disadvantages in TWC performance relative to Pd. The present invention, among other things, addresses these issues. Summary of the invention

[0004] One aspect of the present disclosure relates to a catalyst composition comprising a platinum group metal (PGM) component and a transition metal component, wherein the PGM component comprises platinum (Pt) and the transition metal component is Fe or Cu, and wherein the molar ratio of Pt to transition metal is 0.2 to 10.0.

[0005] Another aspect of the present disclosure relates to a catalytic article for treating exhaust gas, the catalytic article comprising: a substrate, the substrate comprising an inlet end and an outlet end, and having an axial length L; a first catalytic region, the first catalytic region comprising a first platinum group metal (PGM) component and a first transition metal component, wherein the first PGM component comprises platinum (Pt), and the first transition metal component is Fe or Cu, and wherein the molar ratio of Pt to the first transition metal is 0.2 to 10.0.

[0006] The present invention also includes an exhaust system for an internal combustion engine, the exhaust system comprising the three-way catalyst composition of the present invention.

[0007] The present invention also includes treating exhaust gas from an internal combustion engine, in particular treating exhaust gas from a gasoline engine. The method comprises contacting the exhaust gas with a three-way catalyst component of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 An embodiment according to the invention is shown comprising a first catalytic region (monolayer) having a length of 100% of the axial length L of the substrate.

[0009] Figure 2a It is shown that according to one embodiment of the present invention, the first catalytic region extends 100% of the axial length L as a bottom layer; and the second catalytic region extends 100% of the axial length L as a top layer.

[0010] Figure 2b Depicted Figure 2a variants.

[0011] Figure 3a According to one embodiment of the present invention, the first catalytic zone extends from the inlet end to less than 100% of the axial length L; the second catalytic zone extends from the outlet end to less than 100% of the axial length L. The total length of the second catalytic zone and the first catalytic zone is equal to or less than the axial length L.

[0012] Figure 3b Depicted Figure 3a variants.

[0013] Figure 3c According to one embodiment of the present invention, the first catalytic zone extends less than 100% of the axial length L from the inlet end; the second catalytic zone extends less than 100% of the axial length L from the outlet end. The total length of the second catalytic zone and the first catalytic zone is greater than the axial length L.

[0014] Figure 3d Depiction Figure 3c variants.

[0015] Figure 4a The Pt states of Comparative Catalyst A and Catalyst C evaluated by X-ray diffraction (XRD) are shown.

[0016] Figure 4b The Pt states of Comparative Catalyst A and Catalyst F evaluated by XRD are shown. DETAILED DESCRIPTION

[0017] The present invention relates to the catalytic treatment of combustion exhaust gases, such as those produced by gasoline and other engines, and to related catalyst compositions, catalytic articles and systems. More particularly, the present invention relates to the simultaneous treatment of NO in vehicle exhaust systems. x, CO and HC. Although most of the technical development of TWC has focused on Pd-based catalysts, the high dependence on Pd dosage will cause serious economic and environmental problems, such as a sharp rise in PGM prices and the depletion of PGM natural resources. The use of Pt is a promising method for achieving flexible utilization of Pd and / or Pt, but the catalytic activity of Pt in TWC may be low and has been identified as a key technical issue. The inventors have surprisingly found that by doping with transition metal components Fe or Cu, the Pt-based catalyst is functionalized. The inventors have found that the present invention improves the potential performance of TWC in ignition and A / F window performance tests. The method of the present invention also helps to achieve the economic benefits of saving PGM natural resources and environmental sustainability.

[0018] One aspect of the present disclosure relates to a catalyst composition comprising a platinum group metal (PGM) component and a transition metal component, wherein the PGM component comprises platinum (Pt) and the transition metal component is Fe or Cu, and wherein the molar ratio of Pt to transition metal is 0.2 to 10.0.

[0019] Through intensive research, the present inventors have discovered that by incorporating small amounts of transition metals (such as Fe or Cu) ("TM") into Pt-containing TWC catalyst compositions, these novel compositions have demonstrated excellent catalytic properties (e.g., THC / NMHC, CO and NO x All catalytic conversions of can be improved by doping TM into Pt-based catalysts as described in the present invention.

[0020] The molar ratio of Pt to transition metal is based on the metal element. In some embodiments, the molar ratio of Pt to transition metal in the catalyst composition can be 0.2 to 5.0, 0.5 to 5.0, 0.2 to 3.0, or 0.2 to 2.0.

[0021] In some embodiments, the PGM component may further comprise palladium, rhodium, or a combination thereof. In other embodiments, the catalyst composition is substantially free of other PGM components other than platinum.

[0022] The catalyst composition may further comprise an oxygen storage capacity (OSC) material and / or an inorganic oxide.

[0023] The OSC material can be ceria, zirconia, ceria-zirconia mixed oxide, alumina-ceria-zirconia mixed oxide or a combination thereof. More preferably, the OSC material comprises ceria-zirconia mixed oxide, alumina-ceria-zirconia mixed oxide or a combination thereof. The ceria-zirconia mixed oxide may further comprise a dopant, such as lanthanum oxide, neodymium oxide, praseodymium oxide, yttrium oxide, etc. In addition, the OSC material can be used as a support material for the PGM component. In some embodiments, the OSC material comprises ceria-zirconia mixed oxide and alumina-ceria-zirconia mixed oxide.

[0024] The inorganic oxide is preferably an oxide of an element of Groups 2, 3, 4, 5, 13 and 14. Preferably, the inorganic oxide is selected from alumina, magnesia, silica, zirconia, barium oxide, and mixed oxides or composite oxides thereof. Particularly preferably, the inorganic oxide is alumina, lanthanum-alumina, zirconia, or a magnesia / alumina composite oxide. A particularly preferred inorganic oxide is alumina or lanthanum-alumina.

[0025] The weight ratio of the OSC material and the inorganic oxide may be no greater than 10:1; preferably, no greater than 8:1 or 5:1; more preferably, no greater than 4:1 or 3:1; most preferably, no greater than 2:1.

[0026] Alternatively, the weight ratio of OSC material to inorganic oxide may be 10:1 to 1:10; preferably 8:1 to 1:8 or 5:1 to 1:5; more preferably 4:1 to 1:4 or 3:1 to 1:3; and most preferably 2:1 to 1:2.

[0027] In some embodiments, the weight ratio of OSC material to inorganic oxide may be not less than 2: 1. In other embodiments, the weight ratio of OSC material to inorganic oxide may be not less than 10: 1. In another other embodiment, the weight ratio of OSC material to inorganic oxide may be not less than 20: 1 or not less than 30: 1. In yet another other embodiment, the weight ratio of OSC material to inorganic oxide may be not less than 40: 1 or not less than 50: 1.

[0028] The catalyst composition may further comprise an alkali metal or an alkaline earth metal. In other embodiments, the catalyst composition may be substantially free of alkali metals or alkaline earth metals.

[0029] The alkali metal or alkaline earth metal is preferably barium or strontium and mixed oxides or composite oxides thereof. Preferably, the barium or strontium (when present) is loaded in an amount of 0.1 wt % to 15 wt %, and more preferably 3 wt % to 10 wt % of barium or strontium, based on the total weight of the catalyst composition.

[0030] Preferably, the barium or strontium is present in the form of BaCO3 or SrCO3. Such materials may be preformed by any method known in the art, such as incipient wetness impregnation or spray drying.

[0031] In some embodiments, the Pt loading in the catalyst composition may be 0.2 wt % to 10 wt %, 0.5 wt % to 5 wt %, or 1 wt % to 5 wt %.

[0032] TM can be incorporated into the catalyst composition in various ways. In some embodiments, TM can be incorporated into the OSC material as a dopant. In other embodiments, TM can be incorporated into the inorganic oxide as a dopant. In other embodiments, TM can be incorporated into the catalyst composition as a simple physical mixture (e.g., a physical blend). For example, TM can be incorporated as an oxide to be physically blended with the OSC material and / or the inorganic oxide. In other embodiments, TM can be incorporated into the OSC material framework (e.g., TM is doped into the lattice of the formed OSC solid solution material). In certain embodiments, TM can be incorporated into the catalyst composition according to any combination of the embodiments described above, for example, in some embodiments, at least some TM components can be supported on an inorganic oxide.

[0033] In some embodiments, the catalyst composition may include no more than 10 wt%, no more than 5 wt%, or no more than 2 wt% of the TM component (on an elemental basis), based on the total weight of the catalyst composition.

[0034] Throughout the application, "wt% TM" is calculated on an elemental basis.

[0035] As demonstrated in the examples below, the catalyst composition of this aspect can be applied as a TWC catalyst for treating exhaust gas produced by a gasoline engine.

[0036] Another aspect of the present disclosure relates to a catalytic article for treating exhaust gas, the catalytic article comprising: a substrate, the substrate comprising an inlet end and an outlet end, and having an axial length L; a first catalytic region, the first catalytic region comprising a first platinum group metal (PGM) component and a first transition metal component, wherein the first PGM component comprises platinum (Pt), and the first transition metal component is Fe or Cu, and wherein the molar ratio of Pt to the first transition metal is 0.2 to 10.0.

[0037] The first catalytic zone

[0038] The molar ratio of Pt to the first transition metal is based on the metal element. In some embodiments, the molar ratio of Pt to the first transition metal in the catalyst composition can be 0.2 to 5.0, 0.5 to 5.0, 0.2 to 3.0, or 0.2 to 2.0.

[0039] In some embodiments, the first PGM component may further comprise palladium, rhodium, or a combination thereof. In other embodiments, the first catalytic zone is substantially free of other PGM components other than platinum.

[0040] The first catalytic region may further comprise a first oxygen storage capacity (OSC) material and / or a first inorganic oxide.

[0041] The first OSC material can be ceria, zirconia, ceria-zirconia mixed oxide, alumina-ceria-zirconia mixed oxide or a combination thereof. More preferably, the first OSC material comprises ceria-zirconia mixed oxide, alumina-ceria-zirconia mixed oxide or a combination thereof. Ceria-zirconia mixed oxide may also contain dopants such as lanthanum oxide, neodymium oxide, praseodymium oxide, yttrium oxide, etc. The first OSC material may be used as a support material for the first PGM component (e.g., as a first PGM support material). In some embodiments, the first OSC material comprises ceria-zirconia mixed oxide and alumina-ceria-zirconia mixed oxide.

[0042] The first inorganic oxide is preferably an oxide of an element of Groups 2, 3, 4, 5, 13 and 14. Preferably, the first inorganic oxide is selected from alumina, magnesia, silica, zirconia, barium oxide, and mixed oxides or composite oxides thereof. Particularly preferably, the first inorganic oxide is alumina, lanthanum-alumina, zirconia, or a magnesia / alumina composite oxide. A particularly preferred first inorganic oxide is alumina or lanthanum-alumina.

[0043] The weight ratio of the first OSC material to the first inorganic oxide may be no greater than 10:1, preferably no greater than 8:1 or 5:1, more preferably no greater than 4:1 or 3:1, most preferably no greater than 2:1.

[0044] Alternatively, the weight ratio of the first OSC material to the first inorganic oxide may be 10:1 to 1:10, preferably 8:1 to 1:8 or 5:1 to 1:5; more preferably 4:1 to 1:4 or 3:1 to 1:3; and most preferably 2:1 to 1:2.

[0045] In some embodiments, the weight ratio of the first OSC material to the first inorganic oxide may be no less than 2: 1. In further embodiments, the weight ratio of the first OSC material to the first inorganic oxide may be no less than 10: 1. In yet another further embodiment, the weight ratio of the first OSC material to the first inorganic oxide may be no less than 20: 1 or no less than 30: 1. In yet another further embodiment, the weight ratio of the first OSC material to the first inorganic oxide may be no less than 40: 1 or no less than 50: 1.

[0046] The first catalytic region may further comprise a first alkali metal or alkaline earth metal. In other embodiments, the first catalytic region is substantially free of a first alkali metal or alkaline earth metal. The first alkali metal or alkaline earth metal is preferably barium or strontium and a mixed oxide or composite oxide thereof. Preferably, the barium or strontium (when present) is loaded in an amount of 0.1 wt % to 15 wt %, and more preferably 3 wt % to 10 wt % of barium or strontium, based on the total weight of the first catalytic region.

[0047] Preferably, the barium or strontium is present in the form of BaCO3 or SrCO3. Such materials may be preformed by any method known in the art, such as incipient wetness impregnation or spray drying.

[0048] In some embodiments, the Pt loading in the first catalytic zone may be 5 g / ft 3 Up to 300g / ft 3 , 10g / ft 3 Up to 200g / ft 3 or 50g / ft 3 Up to 150g / ft 3 .

[0049] The TM may be incorporated into the first catalytic region in various ways. In some embodiments, the TM may be incorporated into the first OSC material as a dopant. In other embodiments, the TM may be incorporated into the first inorganic oxide as a dopant. In yet other embodiments, the TM may be incorporated into the first catalytic region as a simple physical mixture (e.g., a physical blend). For example, the TM may be incorporated as an oxide to be physically blended with the first OSC material and / or the first inorganic oxide. In other embodiments, the TM may be incorporated into the first OSC material framework (e.g., the TM is doped into the lattice of the formed OSC solid solution material). In certain embodiments, the TM may be incorporated into the first catalytic region according to any combination of the embodiments described above, for example, in some embodiments, at least some of the TM components may be supported on the first inorganic oxide.

[0050] In some embodiments, the first catalytic zone may comprise no more than 10 wt%, no more than 5 wt%, or no more than 2 wt% of the first TM component (on an elemental basis).

[0051] As demonstrated in the following examples, the catalyst articles of this aspect can be applied as a TWC catalyst for treating exhaust gas produced by a gasoline engine.

[0052] The first catalytic region may extend over 100% of the axial length L (see, e.g. Figure 1 , Figure 2a and Figure 2b ). In some embodiments, the first catalytic region may extend from 20% to 99%, 30% to 90%, or 40% to 80% of the axial length L. Alternatively, the first catalytic region may extend from 30% to 70% of the axial length L. Preferably, from 40% to 60% of the axial length L, more preferably from 45% to 55% of the axial length L (see, for example, Figures 3a to 3d ).

[0053] The total washcoat loading of the first catalytic zone may be less than 3.5 g / in 3 , preferably less than 3.0 g / in 3 or 2.5g / in 3 Alternatively, the total washcoat loading for the first catalytic zone may be 0.5 g / in 3 Up to 3.5g / in 3 ; preferably 0.6g / in 3 Up to 3g / in 3 or 0.7g / in 3 Up to 2.5g / in 3 .

[0054] The second catalytic region

[0055] The catalytic article may further include a second catalytic region.

[0056] The second catalytic region may further comprise a second PGM component, a second oxygen storage capacity (OSC) material, a second alkali metal or alkaline earth metal component and / or a second inorganic oxide.

[0057] The second PGM component may be selected from platinum, palladium, rhodium, and mixtures thereof. In some embodiments, the second PGM component may be Pd, Rh, or mixtures thereof.

[0058] The second OSC material can be ceria, zirconia, ceria-zirconia mixed oxide, alumina-ceria-zirconia mixed oxide, or a combination thereof. More preferably, the second OSC material comprises ceria-zirconia mixed oxide, alumina-ceria-zirconia mixed oxide, or a combination thereof. In addition, the second OSC material may also comprise one or more dopants, such as lanthanum, neodymium, praseodymium, yttrium, etc. In addition, the second OSC material may have the function of being used as a support material for the second PGM component. In some embodiments, the second OSC material comprises ceria-zirconia mixed oxide and alumina-ceria-zirconia mixed oxide.

[0059] The weight ratio of zirconium oxide to ceria of the ceria-zirconia mixed oxide may be as follows: at least 50:50, preferably higher than 60:40, more preferably higher than 70:30. Alternatively, the ceria-zirconia mixed oxide may also have a weight ratio of ceria to zirconium oxide of less than 50:50, preferably less than 40:60, more preferably less than 30:70.

[0060] The second OSC material (eg, ceria-zirconia mixed oxide) may be 10 to 90 wt%; preferably 25 to 75 wt%; more preferably 30 to 60 wt% based on the total washcoat loading of the second catalytic zone.

[0061] The second OSC material loading in the second catalytic zone may be less than 2 g / in 3 In some embodiments, the second OSC material loading in the second catalytic zone is no greater than 1.5 g / in 3 、1.2g / in 3 , 1g / in 3 、0.8g / in 3 or 0.7g / in 3 .

[0062] The second alkali metal or alkaline earth metal is preferably barium, strontium, a mixed oxide or a composite oxide thereof. Preferably, the barium or strontium (when present) is in an amount of 0.1 wt % to 15 wt %, and more preferably 3 wt % to 10 wt % barium or strontium based on the total weight of the second catalytic region.

[0063] Even more preferably, the second alkali or alkaline earth metal is strontium.Strontium (when present) is preferably present in an amount of 0.1 to 15 wt%, and more preferably 3 to 10 wt%, based on the total weight of the second catalytic region.

[0064] It is also preferred that the second alkali metal or alkaline earth metal is a mixed oxide or composite oxide of barium and strontium. Preferably, the mixed oxide or composite oxide of barium or strontium is present in an amount of 0.1 wt % to 15 wt %, and more preferably 3 wt % to 10 wt %, based on the total weight of the second catalytic region. It is more preferred that the second alkali metal or alkaline earth metal is a composite oxide of barium and strontium.

[0065] Preferably, the barium or strontium is present in the form of BaCO3 or SrCO3. Such materials may be preformed by any method known in the art, such as incipient wetness impregnation or spray drying.

[0066] The second inorganic oxide is preferably an oxide of an element of Groups 2, 3, 4, 5, 13 and 14. Preferably, the second inorganic oxide is selected from alumina, magnesia, silica, zirconia, barium oxide, and mixed oxides or composite oxides thereof. Particularly preferably, the second inorganic oxide is alumina, lanthanum-alumina, zirconia, or a magnesia / alumina composite oxide. A particularly preferred second inorganic oxide is alumina or lanthanum-alumina.

[0067] The second OSC material and the second inorganic oxide may have a weight ratio of: no greater than 10:1; preferably no greater than 8:1 or 5:1; more preferably no greater than 4:1 or 3:1; most preferably no greater than 2:1.

[0068] Alternatively, the weight ratio of the second OSC material to the second inorganic oxide may be 10:1 to 1:10, preferably 8:1 to 1:8 or 5:1 to 1:5; more preferably 4:1 to 1:4 or 3:1 to 1:3; and most preferably 2:1 to 1:2.

[0069] In some embodiments, the weight ratio of the second OSC material to the second inorganic oxide may be no less than 2: 1. In further embodiments, the weight ratio of the second OSC material to the second inorganic oxide may be no less than 10: 1. In yet another further embodiment, the weight ratio of the second OSC material to the second inorganic oxide may be no less than 20: 1 or no less than 30: 1. In yet another further embodiment, the weight ratio of the second OSC material to the second inorganic oxide may be no less than 40: 1 or no less than 50: 1.

[0070] The total washcoat loading of the second catalytic zone may be less than 3.5 g / in 3 , preferably less than 3.0 g / in 3 or 2.5g / in 3 Alternatively, the total washcoat loading for the first catalytic zone may be 0.5 g / in 3 Up to 3.5g / in 3 ; preferably 0.6g / in3 Up to 3g / in 3 or 0.7g / in 3 Up to 2.5g / in 3 .

[0071] The second catalytic region may extend 100% of the axial length L (see, e.g., Figure 2a and Figure 2b ).

[0072] The second catalytic zone may extend from 30% to 70% of the axial length L. Preferably from 40% to 60% of the axial length L, more preferably from 45% to 55% of the axial length L, and most preferably the combined length of the second zone and the first zone is equal to or greater than the axial length L (see, for example, Figures 3a to 3d ).

[0073] The second catalytic region may overlap the first catalytic region by 0.1% to 99% of the axial length L (see, e.g., Figure 3c and Figure 3d , the first catalytic region may cover the second catalytic region or the second catalytic region may cover the first catalytic region). Alternatively, the total length of the second catalytic region and the first catalytic region may be equal to the axial length L (for example, see Figure 3a and Figure 3b In yet another alternative, the total length of the second catalytic region and the first catalytic region may be less than the axial length L, for example, no more than 95%, 90%, 80% or 70% of the axial length L.

[0074] In some embodiments, the first catalytic region may be supported / deposited directly on the substrate. In certain embodiments, the second catalytic region may be supported / deposited directly on the substrate.

[0075] The catalyst preparation of the present invention may comprise additional components known to the skilled person. For example, the composition of the present invention may also comprise at least one binder and / or at least one surfactant. In the case of a binder, a dispersible alumina binder is preferred.

[0076] Base

[0077] Preferably, the substrate is a flow-through monolith. Alternatively, the substrate may be a wall-flow filter.

[0078] The flow-through monolith substrate has a first face and a second face defining a longitudinal direction therebetween. The flow-through monolith substrate has a plurality of channels extending between the first face and the second face. The plurality of channels extend in the longitudinal direction and provide a plurality of interior surfaces (e.g., surfaces defining the walls of each channel). Each channel of the plurality of channels has an opening at the first face and an opening at the second face. For the avoidance of doubt, the flow-through monolith substrate is not a wall flow filter.

[0079] The first face is typically at the inlet end of the substrate and the second face is at the outlet end of the substrate.

[0080] The channel may have a constant width, and the plurality of channels may each have a uniform channel width.

[0081] Preferably, in a plane orthogonal to the longitudinal direction, the monolithic substrate has 300 to 900 channels / square inch, preferably 400 to 800 channels / square inch. For example, on the first side, the density of the open first channels and the closed second channels is 600 to 700 channels / square inch. The channels may have a cross section of: rectangular, square, circular, elliptical, triangular, hexagonal, or other polygonal shapes.

[0082] The monolith substrate acts as a support for holding the catalytic material. Suitable materials for forming the monolith substrate include ceramic-like materials such as cordierite, silicon carbide, silicon nitride, zirconium oxide, mullite, spodumene, alumina-silica magnesia or zirconium silicate, or porous refractory metals. Such materials and their use in making porous monolith substrates are well known in the art.

[0083] It should be noted that the flow-through monolithic substrate described herein is a single component (i.e., a single brick). Nevertheless, when forming an emission treatment system, the substrate used can be formed by adhering multiple channels together or by adhering multiple smaller substrates together, as described herein. Such techniques, as well as suitable housings and configurations for emission treatment systems, are well known in the art.

[0084] In embodiments where the catalyst article of the invention comprises a ceramic substrate, the ceramic substrate may be made of any suitable refractory material, such as alumina, silica, ceria, zirconium oxide, magnesium oxide, zeolites, silicon nitride, silicon carbide, zirconium silicate, magnesium silicate, aluminosilicates, and metal aluminosilicates (such as cordierite and spodumene), or mixtures or mixed oxides of any two or more thereof. Cordierite, magnesium aluminosilicate, and silicon carbide are particularly preferred.

[0085] In embodiments where the catalyst article of the present invention comprises a metal substrate, the metal substrate may be made of any suitable metal, and in particular, of heat-resistant metals and metal alloys, such as titanium and stainless steel, and ferritic alloys containing iron, nickel, chromium and / or aluminum in addition to other trace metals.

[0086] Another aspect of the present disclosure relates to using the catalyst articles described herein to treat x A catalytic converter equipped with a TWC made according to this method shows improved catalytic properties compared to a conventional TWC (at the same PGM loading), and also shows particularly improved performance during the cold start phase and better THC light-off performance (e.g., see Examples 1 and 2; and Tables 2 to 4).

[0087] Another aspect of the present disclosure relates to a system for treating vehicle exhaust, the system comprising a catalyst article as described herein, together with a conduit for transferring the exhaust through the system.

[0088] definition

[0089] As used herein, the term "region" refers to an area on a substrate, which is generally obtained by drying and / or calcining a washcoat. For example, a "region" can be arranged or carried on a substrate in the form of a "layer" or "zone". The region or arrangement on the substrate is generally controlled during the application of the washcoat to the substrate. A "region" generally has distinct boundaries or edges (i.e., one region can be distinguished from another region using conventional analytical techniques).

[0090] Typically, a "region" has a substantially uniform length. In this context, reference to a "substantially uniform length" refers to a length that does not deviate from its average value (e.g., the difference between the maximum length and the minimum length) by more than 10%, preferably does not deviate by more than 5%, more preferably does not deviate by more than 1%.

[0091] Preferably each "region" has a substantially uniform composition (i.e., the composition of the washcoat does not differ significantly when comparing one portion of the region to another portion of the region). In this context, a substantially uniform composition refers to a material (e.g., region) in which the difference in composition when comparing one portion of the region to another portion of the region is 5% or less, typically 2.5% or less, and most typically 1% or less.

[0092] As used herein, the term "region" refers to an area having a length less than the total length of a substrate, such as ≤75% of the total length of the substrate."Regions" typically have a length (i.e., substantially uniform length) of at least 5% (e.g., ≥5%) of the total length of the substrate.

[0093] The overall length of a substrate is the distance between its inlet end and its outlet end (eg, opposite ends of the substrate).

[0094] As used herein, any reference to a "zone disposed at the inlet end of a substrate" refers to a zone disposed or carried on a substrate, wherein the zone is closer to the inlet end of the substrate than a zone near the outlet end of the substrate. Thus, the midpoint of the zone is closer to the inlet end of the substrate than the midpoint near the outlet end of the substrate (i.e., at half its length). Similarly, as used herein, any reference to a "zone disposed at the outlet end of a substrate" refers to a zone disposed or carried on a substrate, wherein the zone is closer to the outlet end of the substrate than a zone near the inlet end of the substrate. Thus, the midpoint of the zone is closer to the outlet end of the substrate than the midpoint near the inlet end of the substrate (i.e., at half its length).

[0095] When the substrate is a wall flow filter, generally speaking, any reference to a "zone disposed at the inlet end of the substrate" refers to a zone disposed or carried on the substrate that:

[0096] (a) a region closer to the inlet end (e.g., open end) of an inlet channel of the substrate than a region closer to the closed end (e.g., plugged end or blocked end) of the inlet channel, and / or

[0097] (b) A closed end (eg, a plugged or blocked end) of an outlet channel of the substrate is closer than a region closer to the outlet end (eg, an open end) of the outlet channel.

[0098] Thus, the midpoint of the zone (i.e., at half its length) is (a) closer to the inlet end of the inlet channel of the substrate than the midpoint near the closed end of the inlet channel, and / or (b) closer to the closed end of the outlet channel of the substrate than the midpoint near the outlet end of the outlet channel.

[0099] Similarly, when the substrate is a wall flow filter, any reference to a "zone disposed at the outlet end of the substrate" refers to a zone disposed or carried on the substrate that:

[0100] (a) a region closer to the outlet end (e.g., the open end) of the outlet channel of the substrate than a region closer to the closed end (e.g., the blocked end or the plugged end) of the outlet channel, and / or

[0101] (b) A closed end (eg, a plugged or blocked end) of an inlet channel of the substrate is closer than a region closer to the inlet end (eg, an open end) of the inlet channel.

[0102] Thus, the midpoint of the zone (i.e., at half its length) is (a) closer to the outlet end of the outlet channel of the substrate than the midpoint near the closed end of the outlet channel, and / or (b) closer to the closed end of the inlet channel of the substrate than the midpoint near the inlet end of the inlet channel.

[0103] When the washcoat layer is present in the wall of a wall flow filter (ie, the zone is in the wall), the zone may satisfy both (a) and (b) simultaneously.

[0104] The term "washcoat" is well known in the art and refers to an adherent coating typically applied to a substrate during catalyst production.

[0105] As used herein, the acronym "PGM" refers to "platinum group metals". The term "platinum group metals" generally refers to metals selected from Ru, Rh, Pd, Os, Ir and Pt, preferably metals selected from Ru, Rh, Pd, Ir and Pt. Generally speaking, the term "PGM" preferably refers to metals selected from Rh, Pt and Pd.

[0106] As used herein, the term "mixed oxide" generally refers to a mixture of oxides in a single phase, as generally known in the art. As used herein, the term "composite oxide" generally refers to a composition of oxides having more than one phase, as generally known in the art.

[0107] As used herein, the expression "consisting essentially of limits the scope of a feature to include the specified materials or steps, and any other materials or steps that do not materially affect the basic characteristics of the feature, such as trace impurities. The expression "consisting essentially of encompasses the expression "consisting of.

[0108] As used herein, the expression "substantially free" used for a material in the context of the content of a region, layer or zone generally refers to a small amount of material, such as ≤5 wt%, preferably ≤2 wt%, more preferably ≤1 wt%. The expression "substantially free" encompasses the expression "does not comprise".

[0109] As used herein, the expression "substantially free" used for a material in the context of the content of a region, layer or zone generally means that the material is in trace amounts, such as ≤1 wt%, preferably ≤0.5 wt%, more preferably ≤0.1 wt%. The expression "substantially free" encompasses the expression "does not comprise".

[0110] As used herein, any reference to the amount of dopant (particularly the total amount) expressed as wt % refers to the weight of the support material or refractory metal oxide thereof.

[0111] As used herein, the term "loading" refers to the weight of the metal in g / ft. 3 The measurement result is in units of .

[0112] The following examples merely illustrate the present invention. Those skilled in the art will recognize many variations within the spirit of the present invention and the scope of the claims.

[0113] Example

[0114] Example 1: Improvement of light-off and A / F window performance by Fe doping

[0115] Comparative Catalyst A :

[0116] Comparative Catalyst A is a single layer TWC coated on a ceramic substrate (400 cpsi, 4.0 mil wall thickness). The catalytic region consists of Pt supported on a washcoat of CeZr mixed oxide, La stabilized alumina using a platinum nitrate precursor. The washcoat loading of the catalytic region is about 2 g / in 3 , where the Pt loading is 100g / ft 3 .

[0117] Catalyst B :

[0118] Catalyst B is a single layer TWC coated on a ceramic substrate (400 cpsi, 4.0 mil wall thickness). The catalytic region consists of Pt supported on a washcoat of CeZr mixed oxide, La stabilized alumina using a platinum nitrate precursor. The washcoat loading of the catalytic region is about 2 g / in 3 , where the Pt loading is 100g / ft 3 The molar ratio of Pt to Fe was 10:1.

[0119] Catalyst C :

[0120] Catalyst C is a single layer TWC coated on a ceramic substrate (400 cpsi, 4.0 mil wall thickness). The catalytic region consists of Pt supported on a washcoat of CeZr mixed oxide, La stabilized alumina using a platinum nitrate precursor. The washcoat loading of the catalytic region is about 2 g / in 3 , where the Pt loading is 100g / ft 3 The molar ratio of Pt to Fe was 0.8:1.

[0121] Catalyst D :

[0122] Catalyst D is a single layer TWC coated on a ceramic substrate (400 cpsi, 4.0 mil wall thickness). The catalytic region consists of Pt supported on a washcoat of CeZr mixed oxide, La stabilized alumina using a platinum nitrate precursor. The washcoat loading of the catalytic region is about 2 g / in 3 , where the Pt loading is 100g / ft 3 and Fe is 5.0 wt% (calculated as Fe). The molar ratio of Pt to Fe is about 0.2:1.

[0123] Comparative Catalyst A and Comparative Catalysts B to D were tested individually on a synthetic catalyst activity test (SCAT) apparatus. The light-off performance was tested in a gas stream of 5 vol% H2O + 15 vol% CO2 + 0.2 vol% H2 + 1260 ppm C C3H6 + 0.6 vol% CO + 0.6 vol% O2 + 1000 ppm NO balanced with N2 and a temperature ramp of 20°C / min. HC, CO and NO concentrations were calculated by comparing the feed gas and the catalyst outlet gas concentrations. x Comparative Catalyst A and Catalysts B to D were hydrothermally aged at 1050° C. for 4 hours under the redox conditions of Table 1.

[0124] Table 1

[0125] condition <![CDATA[C3H6(%)]]> <![CDATA[O2(%)]]> <![CDATA[H2O(%)]]> <![CDATA[N2]]> Duration reduction 2.0 0.8 8 margin 80sec Oxidation 0 20 10 margin 20sec

[0126] T of HC and CO of aged catalyst A and catalysts B to D 80 Ignition temperature and NO x The η = 320 ° C light-off conversion of 100 ℃ is shown in Table 2. When compared with Comparative Catalyst A, Catalyst C of the present invention greatly improves the light-off performance, wherein for HC and CO, T 80 (T 80 is the temperature when the conversion rate reaches 80%), respectively, and for NO x , η=320℃ (η=320℃ is the conversion rate when the temperature reaches 320℃) increased by about 3%.

[0127] Table 2: Ignition performance results

[0128]

[0129] The A / F window performance of Comparative Catalyst A and Catalyst C was tested by SCAT in a gas flow from A / F=15.4 (10 vol% H2O + 14 vol% CO2 + 0.17 vol% H2 + 1200 ppm C C3H6 + 0.5 vol% CO + 1.54 vol% O2 + 500 ppm NO balanced with N2) to A / F=14.0 (10 vol% H2O + 14 wt% CO2 + 0.7 vol% H2 + 1200 ppm C C3H6 + 2.11 vol% CO + 0.5 vol% O2 + 500 ppm NO balanced with N2) and a temperature of 300°C / min. The CO-rich and NO-rich gas concentrations were calculated by comparing the concentrations of the feed gas and the gas at the catalyst outlet. xThe conversion rate of CO and NO under the rich condition of A / F < 14.5 for the aged comparative catalyst A and catalyst C x The conversions are shown in Table 2. When compared with Comparative Catalyst A, Catalyst C of the present invention greatly improves the CO-rich and NO-rich x performance.

[0130] Table 3: SCAT A / F Window Performance (Conversion Rate / %) Results

[0131]

[0132]

[0133] The Pt states of Comparative Catalyst A and Catalyst C were evaluated by X-ray diffraction (XRD). Figure 4a As shown, although for Comparative Catalyst A, a peak attributed to Pt particles was obtained at about 39.7 degrees, for Catalyst C, formation of a Pt-Fe alloy having a diffraction peak was observed at about 40.3 degrees.

[0134] Example 2: Improving ignition performance by Cu doping

[0135] Catalyst E :

[0136] Catalyst E is a single layer TWC coated on a ceramic substrate (400 cpsi, 4.0 mil wall thickness). The catalytic region consists of Pt supported on a washcoat of CeZr mixed oxide, La stabilized alumina using a platinum nitrate precursor. The washcoat loading of the catalytic region is about 2 g / in 3 , wherein the Pt loading is 100 g / ft3 and the Cu is 0.2 wt% (calculated as Cu). The molar ratio of Pt to Cu is 5:1.

[0137] Catalyst F :

[0138] Catalyst F is a single layer TWC coated on a ceramic substrate (400 cpsi, 4.0 mil wall thickness). The catalytic region consists of Pt supported on a washcoat of CeZr mixed oxide, La stabilized alumina using a platinum nitrate precursor. The washcoat loading of the catalytic region is about 2 g / in 3 , where the Pt loading is 100g / ft 3 The molar ratio of Pt to Cu is 2:1.

[0139] Catalyst G :

[0140] Catalyst G is a single layer TWC coated on a ceramic substrate (400 cpsi, 4.0 mil wall thickness). The catalytic region consists of Pt supported on a washcoat of CeZr mixed oxide, La stabilized alumina using a platinum nitrate precursor. The washcoat loading of the catalytic region is about 2 g / in 3 , where the Pt loading is 100g / ft 3 The molar ratio of Pt to Cu is 1:1.

[0141] Comparative Catalyst A and Comparative Catalysts E to G were tested individually on a synthetic catalyst activity test (SCAT) apparatus. The light-off performance was tested in a gas stream of 10 vol% H2O + 15 vol% CO2 + 0.2 vol% H2 + 1260 ppm C C3H6 + 0.6 vol% CO + 0.6 vol% O2 + 1000 ppm NO balanced with N2 and a temperature ramp of 20°C / min. HC, CO and NO concentrations were calculated by comparing the feed gas and the catalyst outlet gas concentrations. x Comparative Catalyst A and Catalysts G to I were hydrothermally aged at 1050° C. for 4 hours under the redox conditions of Table 1.

[0142] T of HC and CO of aged catalyst A and catalysts F to G 50 Ignition temperature and NO x The η = 300 ° C light-off conversion of 100 ℃ is shown in Table 4. When compared with Comparative Catalyst A, Catalyst F of the present invention greatly improves the light-off performance, wherein for HC and CO, T 50 (T 50 The temperature at which the conversion rate reaches 50% was reduced by about 92°C and 85°C, respectively. Similar NO x Conversion performance.

[0143] Table 4: SCAT ignition performance results

[0144]

[0145] The Pt state of Comparative Catalyst A and Catalyst F was evaluated by XRD. Figure 4b As shown, although for Comparative Catalyst A, a peak attributed to Pt particles was obtained at about 39.8 degrees, for Catalyst F, formation of a Pt-Cu alloy having a diffraction peak was observed at about 40.3 degrees.

Claims

1. A catalyst composition comprising a platinum group metal (PGM) component and a transition metal component, wherein: The PGM component includes platinum (Pt), and the transition metal component is Fe or Cu, and wherein a molar ratio of Pt to the transition metal is 0.2 to 10.

0.

2. The catalyst composition according to claim 1, further comprising an oxygen storage capacity (OSC) material, an inorganic oxide and / or an alkali metal or an alkaline earth metal.

3. The catalyst composition according to claim 2, wherein The OSC material is selected from cerium oxide, zirconium oxide, ceria-zirconia mixed oxide, and alumina-ceria-zirconia mixed oxide.

4. The catalyst composition according to claim 2 or claim 3, wherein The inorganic oxide is selected from the group consisting of aluminum oxide, magnesium oxide, silicon dioxide, cerium dioxide, barium oxide, and mixed oxides or composite oxides thereof.

5. The catalyst composition according to any one of claims 2 to 4, wherein The alkali metal or alkaline earth metal is barium or strontium, and mixed oxides or composite oxides thereof.

6. The catalyst composition according to any one of claims 2 to 4, wherein The catalyst composition is substantially free of barium.

7. A catalyst composition according to any one of the preceding claims, wherein The PGM component also includes palladium, rhodium, or a mixture thereof.

8. The catalyst composition according to any one of claims 2 to 7, wherein The Pt loading ranged from 0.2 wt% to 10 wt%.

9. The catalyst composition according to any one of the preceding claims, wherein The molar ratio of Pt to the transition metal is 0.2 to 5.

0.

10. The catalyst composition according to any one of the preceding claims, which is a three-way catalyst (TWC).

11. A catalytic product for treating exhaust gas, the catalytic product comprising: a substrate, the substrate including an inlet end and an outlet end and having an axial length L; A first catalytic region, the first catalytic region comprises a first platinum group metal (PGM) component and a first transition metal component, wherein the first PGM component comprises platinum (Pt), and the first transition metal component is Fe or Cu, and wherein the molar ratio of Pt to the first transition metal is 0.2 to 10.

0.

12. The catalytic article according to claim 11, wherein The first catalytic region further comprises a first oxygen storage capacity (OSC) material and / or a first inorganic oxide.

13. The catalytic article according to claim 12, wherein: The first OSC material is selected from cerium oxide, ceria-zirconia mixed oxide, and alumina-ceria-zirconia mixed oxide.

14. A catalytic article according to claim 12 or claim 13, wherein: The first inorganic oxide is selected from the group consisting of aluminum oxide, magnesium oxide, silicon dioxide, zirconium oxide, lanthanum oxide, cerium oxide, neodymium oxide, praseodymium oxide, yttrium oxide, and mixed oxides or composite oxides thereof.

15. The catalytic article according to any one of claims 11 to 14, wherein The molar ratio of Pt in the first catalytic region to the first transition metal is 0.2 to 5.

0.

16. The catalytic article according to any one of the preceding claims, wherein: The first catalytic region contains from 0.1 wt % to 10 wt % of the first transition metal component on an elemental basis.

17. The catalytic article according to any one of the preceding claims, wherein: The Pt loading in the first catalytic zone is 5 g / ft 3 Up to 300g / ft 3 .

18. The catalytic article according to any one of the preceding claims, wherein: The first PGM component further comprises Pd, Rh or a combination thereof.

19. The catalytic article of any preceding claim, further comprising a second catalytic region.

20. The catalytic article of claim 19, wherein: The second catalytic zone comprises a second PGM component.

21. The catalytic article of claim 20, wherein: The second PGM component is selected from the group consisting of platinum, palladium, rhodium, and mixtures thereof.

22. The catalytic article according to any one of claims 19 to 21, wherein The second catalytic region further comprises a second OSC material and / or a second inorganic oxide.

23. The catalytic article of claim 22, wherein: The second OSC material is selected from cerium oxide, zirconium oxide, ceria-zirconia mixed oxide, and alumina-ceria-zirconia mixed oxide.

24. The catalytic article of claim 22 or claim 23, wherein: The second inorganic oxide is selected from the group consisting of aluminum oxide, magnesium oxide, silicon dioxide, zirconium dioxide, lanthanum oxide, cerium oxide, neodymium oxide, praseodymium oxide, yttrium oxide, and mixed oxides or composite oxides thereof.

25. The catalytic article of any one of the preceding claims, wherein the first catalytic region extends the axial length L.

26. The catalytic article according to any one of claims 19 to 25, wherein The second catalytic region extends over the axial length L.

27. The catalytic article according to claim 25 or 26, wherein The first catalytic region is directly supported / deposited on the substrate.

28. The catalytic article of claim 25 or 26, wherein: The second catalytic region is directly supported / deposited on the substrate.

29. The catalytic article according to any one of claims 11 to 24, wherein The first catalytic region extends less than the axial length L.

30. The catalytic article according to any one of claims 19 to 25, wherein The second catalytic region extends less than the axial length L.

31. The catalytic article of claim 29 or 30, wherein: The first catalytic region is directly supported / deposited on the substrate.

32. The catalytic article of claim 29 or 30, wherein: The second catalytic region is directly supported / deposited on the substrate.